Development of a 3-Dimensional Middle Ear Model to Teach Anatomy and Endoscopic Ear Surgical Skills. Issue 4 (October 2021) - Jenks, Carolyn M.; Patel, Vir; Bennett, Brittany; Dunham, Brian; Devine, Conor M.
Mastery of ear anatomy and otologic surgical skills is challenging for trainees, and educational resources are limited. Advancements in 3-dimensional (3D) printing have enabled the construction of complex microscopic models. Otoendoscopy provides excellent visualization and has been shown to enhance anatomic learning. Our aim was to develop a 3D model of the middle ear and external auditory canal using computed tomography images of a pediatric temporal bone for use with otoendoscopes. Resulting models are life sized, anatomically accurate, and allow for identification of relevant middle ear structures. Forty-six trainees were recruited for a pilot study and randomized to study using the model or standard resources. There were no differences in pretest, posttest, or 1-week posttest performance between groups; however, trainees assigned to the model reported higher prospective interest, satisfaction, and subjective improvement. This model may be used with otoendoscopes for anatomic and surgical training and represents an advancement in otologic surgical simulation.